2022
DOI: 10.3389/fphys.2022.842935
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Environmental Conditions on Pacing in Age Group Marathoners Competing in the “New York City Marathon”

Abstract: Background: The two aspects of the influence of environmental conditions on marathon running performance and pacing during a marathon have been separately and widely investigated. The influence of environmental conditions on the pacing of age group marathoners has, however, not been considered yet.Objective: The aim of the present study was to investigate the association between environmental conditions (i.e., temperature, barometric pressure, humidity, precipitation, sunshine, and cloud cover), gender and pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…From recreational runners of all ages to elite athletes, the objectives may differ widely, from being a finisher, to running the race as fast as possible, to winning it and/or breaking records (e.g., personal, national, world records) to win money (i.e., economic reasons) [5,6]. Although long-distance performances, as in the marathon, can be influenced by factors beyond the athlete's control (e.g., climate conditions, seasonal characteristics like temperature, humidity and barometric pressure…) [7,8], they mainly depend on personal characteristics (age, sex, physical qualities, psychological traits and states…) and training variables (tactics, pacing strategy…) [4,[9][10][11][12][13]. For example, Weiss et al [7] showed that temperature and humidity affect pacing in age group marathoners differently (i.e., slowing down for runners of both sexes aged 20-59 with increasing temperature, and slowing down for runners aged under 20 and over 80 with increasing humidity).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…From recreational runners of all ages to elite athletes, the objectives may differ widely, from being a finisher, to running the race as fast as possible, to winning it and/or breaking records (e.g., personal, national, world records) to win money (i.e., economic reasons) [5,6]. Although long-distance performances, as in the marathon, can be influenced by factors beyond the athlete's control (e.g., climate conditions, seasonal characteristics like temperature, humidity and barometric pressure…) [7,8], they mainly depend on personal characteristics (age, sex, physical qualities, psychological traits and states…) and training variables (tactics, pacing strategy…) [4,[9][10][11][12][13]. For example, Weiss et al [7] showed that temperature and humidity affect pacing in age group marathoners differently (i.e., slowing down for runners of both sexes aged 20-59 with increasing temperature, and slowing down for runners aged under 20 and over 80 with increasing humidity).…”
Section: Introductionmentioning
confidence: 99%
“…Although long-distance performances, as in the marathon, can be influenced by factors beyond the athlete's control (e.g., climate conditions, seasonal characteristics like temperature, humidity and barometric pressure…) [7,8], they mainly depend on personal characteristics (age, sex, physical qualities, psychological traits and states…) and training variables (tactics, pacing strategy…) [4,[9][10][11][12][13]. For example, Weiss et al [7] showed that temperature and humidity affect pacing in age group marathoners differently (i.e., slowing down for runners of both sexes aged 20-59 with increasing temperature, and slowing down for runners aged under 20 and over 80 with increasing humidity). Other studies [12,13] indicated that pacing strategy which may also be dependent on the profile of the runners in relation to age (e.g., pace changing is more prominent in younger and older marathoners compared to the other age groups of marathoners) [12] or sex (e.g., men tend to opt more for a "risk" strategy by starting out at fast speeds and then modulating or slowing down afterwards, whereas women tend to err on the side of caution) [13].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations